炎症性状態の処置方法 (2023)
The present invention provides methods for treating inflammatory diseases, or conditions associated with, or resulting in part from, elevated levels of IL-33 and IL-4, in particular inflammatory lung disorders. The methods of the present invention comprise administering to a subject in need thereof one or more therapeutically effective doses of an IL-33 antagonist alone or in combination with one or more therapeutically effective doses of an IL-4R antagonist. In certain embodiments, the methods of the present invention include use of the antagonists to treat any inflammatory disease or condition mediated in part by enhanced IL-33-mediated signaling and IL-4-mediated signaling.